COMPETITION ON THE WHOLESALE MEDICATION DISTRIBUTION MARKET IN ROMANIA - Alina HAGIU; Marinela BARBULESCU; Cristina BALDAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2013)
Wholesale distribution of medicines in Romania was in the constant attention of the competition authority. In order to analyze the operation of the distribution system practiced in Romania, but also changes that may occur in this system on short and medium term, the Competition Council conducted a sector inquiry after which they found some malfunctioning mainly chained to distributors access to certain medications. Conducted on a sample of 23 pharmaceutical groups operating on the Romanian market and holding approximately 80% of the pharmaceutical market in Romania in 2009, the sector inquiry aimed at two objectives, namely: Legislation analysis with impact on the wholesale distribution of drugs; Market analysis of drug distribution.Following the findings of the high concentration of markets analyzed, due to significant market shares held by innovative drugs under investigation were analyzed also the penetration of generics in the market and the factors that led to this situation.